Preparation method of anti-cracking nano-composite coating for single-piece non-heat-insulation fireproof glass
By forming a crack -type nano -composite coating on the fire -resistant glass, combined with nanomaterials and functional membrane substances, the existing fire -resistant glass fire resistance time and limited impact resistance have been solved. life.
Patent Information
- Application Number
- CN202411903905.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing fireproof glass has insufficient fire resistance time and limited impact resistance when dealing with extreme fire conditions, making it difficult to effectively improve its fire resistance.
The dispersant and modifiers are used to combine nano -material and functional membrane substances. The fissure -type nano -composite coating is formed through physical gas phase deposition method or chemical gas deposition method to improve the fire resistance and mechanical properties of coating.
It significantly improves the crack resistance, service life and fire resistance of fire -resistant glass, delay the rupture time of glass in the fire, and enhance its corrosion resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fireproof glass, and in particular to a method for preparing a crack-resistant nano composite coating for a single piece of non-insulating fireproof glass. Background Art
[0002] With the acceleration of urbanization and the continuous emergence of high-rise buildings, the issue of building fire safety has become increasingly prominent. Class C non-insulating monolithic fireproof glass is a special glass with specific fire resistance time requirements, usually used in fire walls, fire doors, fire windows and other parts of buildings. Its main characteristics include maintaining structural integrity at high temperatures, not producing dangerous fragments, and effectively blocking the spread of fire and smoke. The performance of Class C non-insulating monolithic fireproof glass depends on many factors such as its chemical composition, production process, and internal stress distribution. As a special glass material that can maintain integrity for a certain period of time in a fire and prevent the spread of fire and smoke, the importance of Class C non-insulating monolithic fireproof glass is self-evident.
[0003] The patent with the publication number CN116445021A discloses a fire-retardant coating and its preparation method, and fire-retardant glass. The fire-retardant coating includes the following components by weight percentage: 83% to 90% water glass solution; 2% to 9% flame retardant; and 2% to 14% curing agent; the total mass percentage of each component is 100%; the curing agent is glycerol or sodium metabisulfite, or a combination of glycerol and silicon phosphate. The invention uses water glass as the binder of the fire-retardant coating, combined with a specific curing agent that can promote the curing of water glass and maintain a good transparent effect, and is compounded in a physical blending manner. The water-based inorganic transparent fire-retardant coating with excellent physical and chemical properties and fire-retardant properties is obtained by adjusting the raw material ratio, and is used to prepare fire-retardant glass with excellent fire-retardant properties and light weight that can be cured under room temperature and windless conditions.
[0004] The patent with publication number CN115521081B discloses a fireproof layer material for non-insulating composite fireproof glass, whose raw materials are composed of the following substances: 50-500 parts of hydroxylated gas-phase nano-silica particles, 0.5-5 parts of tetraethyl orthosilicate, 50-200 parts of deionized water, 5-20 parts of anti-condensation agent, 0.2-10 parts of carbonizing agent, 0.2-10 parts of carbonizing auxiliary agent, 0.2-10 parts of heat-resistant stabilizer, 0.01-1.5 parts of 2-(trifluoromethyl)acrylic acid, 0.01-1.5 parts of butyl acrylate, 0.01-1.5 parts of methacrylic acid, 0.01-1.5 parts of methyl methacrylate, 0.1-2 parts of ion fixer, 0.01-1.5 parts of storage stabilizer, 0.04-0.5 parts of plasticizer and 17-280 parts of potassium hydroxide with a purity of 85%. The nano core-shell structured organic / inorganic hybrid particles are multi-modal, broadly distributed nanoparticles prepared by using a gradient high-pressure homogenization technique.
[0005] The current fireproof glass still has certain limitations when dealing with extreme fire conditions, such as insufficient fire resistance time and limited impact resistance. Therefore, how to further improve the fireproof performance of Class C non-insulating monolithic fireproof glass has become a top priority for current research. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for preparing a crack-resistant nano-composite coating for a single-piece non-insulating fire-resistant glass. The method combines nano-materials with functional film-forming substances through a dispersant and a modified silane coupling agent, thereby improving the fire resistance and mechanical properties of the coating, and enhancing the interface bonding force and stability of the coating, so that the coating has better crack resistance and service life, and effectively improves the comprehensive performance and application value of the nano-composite layer.
[0007] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0008] A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass comprises the following steps:
[0009] Step (1), adding a dispersant to deionized water, mixing, then adding the nanomaterial, and ultrasonically treating to obtain a pretreated mixed material;
[0010] Step (2), adding a modified silane coupling agent and a functional film-forming substance to the pretreated mixed material, stirring at a speed of 5000-7000 rpm for 5-8 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by physical vapor deposition or chemical vapor deposition to form an anti-cracking nano-composite coating;
[0011] The unique physical and chemical properties of nanomaterials, such as high specific surface area, high activity, and high stability, make nano coatings have significant advantages in improving glass performance. They can form a dense, uniform and functional film layer on the glass surface to optimize the glass performance. Nano coatings act on Class C non-insulating monolithic fireproof glass in four aspects: improving surface hardness and wear resistance, slowing down heat conduction, reducing thermal radiation absorption, and preventing crack expansion, and systematically improve its fireproof performance. Nano coatings build a highly dense and uniform nano film on the surface of fireproof glass through their fine size, morphology, arrangement and distribution. The formation of this film not only significantly increases the microscopic roughness of the glass surface, but also greatly improves the hardness and wear resistance of the glass surface through the strong chemical bonding formed between nanoparticles and the glass matrix. The nano-scale film layer has extremely low thermal conductivity due to its unique physical properties. The mechanism of slowing down heat conduction by nano coatings is actually a precise intervention in the heat transfer path. By forming a multi-layer interface structure, nano coatings change the way heat is transferred, making the heat more obstructed during the transfer process. Nano coatings also have the ability to efficiently manage thermal radiation, which is mainly based on the special optical properties of nanoparticles. Nanomaterial particles can produce reflection and scattering effects, which are fully utilized in nano coatings, thereby significantly reducing the direct thermal radiation absorption of flames on glass. In particular, the absorption rate of radiation of a specific wavelength is adjusted, thereby effectively reducing the accumulation of heat on the glass surface. The high strength characteristics of nano materials themselves also provide a strong physical support for inhibiting the generation and expansion of cracks. Under high temperature conditions, micro cracks often form inside the glass due to thermal stress. However, the existence of nano coatings is like a tough protective barrier. It can not only effectively disperse the stress concentration at the crack tip, thereby slowing down the crack expansion rate, but also completely prevent the crack from extending further in some cases through the bridging effect of nanoparticles. Nano coatings can optimize the stress transmission path, so that the stress is more evenly distributed inside the glass, thereby reducing the phenomenon of stress concentration. At the same time, nano coatings can also block the crack expansion path, so that the crack encounters greater obstacles during the expansion process, thereby slowing down the crack expansion rate. The high strength characteristics of nano materials are also one of the important factors in inhibiting crack expansion. Nanoparticles have extremely high specific surface area and surface activity, and can form strong chemical bonds with the glass matrix, thereby improving the overall strength of the glass. This increase in strength enables the glass to better resist the generation and expansion of cracks when subjected to external forces.
[0012] Functional film-forming substances can form a continuous and dense coating film during the drying or curing process, firmly bonding the nanomaterials and other additives together, giving the coating good adhesion and covering power, enabling the coating to adhere tightly to the surface of the fire-resistant glass to play a protective role. At the same time, it adjusts the comprehensive properties of the coating, such as hardness, flexibility, water resistance, and weather resistance, to meet the requirements of fire-resistant glass in different usage environments.
[0013] Nanomaterials are prone to agglomeration due to their small particle size and large specific surface area. Dispersants can be adsorbed on the surface of nanomaterials, making their surfaces carry the same charge or steric hindrance effect, thereby effectively preventing nanomaterials from agglomerating in the solution and ensuring the uniform distribution of nanomaterials in the coating, thereby improving the overall performance of the coating. Evenly dispersed nanomaterials can better interact with other components to form a stable coating structure. During long-term use, it is not easy to cause problems such as cracking and shedding due to the agglomeration of nanomaterials, thereby improving the stability and service life of the coating.
[0014] Modified silane coupling agents can chemically react with active groups such as hydroxyl groups on the surface of nanomaterials, and can also interact with active groups in functional film-forming substances, thereby forming chemical bonds between nanomaterials and film-forming substances. Through chemical bonding, modified silane coupling agents can significantly improve the interfacial bonding between nanomaterials and film-forming substances, making nanomaterials better fixed in the coating, less likely to fall off or migrate, thereby enhancing the overall performance of the coating. When the coating is subjected to external forces or deformed during use, good interfacial bonding can ensure the integrity of the coating and prevent cracks and peeling.
[0015] The preparation method of the modified silane coupling agent is as follows:
[0016] S1. Mix the silane coupling agent with ethanol, lower the temperature of the mixed solution to -15 to -5°C, add a catalyst, and then drop diethyl maleate under stirring. After the addition, react for 20-30 minutes, then raise the temperature to 20-25°C, react at a constant temperature for 1-2 hours, and purify to obtain an intermediate product;
[0017] S2. Add epichlorohydrin to the intermediate product of S1, react at a temperature of 50-60° C. for 2-4 hours, and distill under reduced pressure to remove excess epichlorohydrin to obtain a modified silane coupling agent.
[0018] Preferably, in steps S1 and S2, the mass ratio of the silane coupling agent, the catalyst, diethyl maleate and epichlorohydrin is 1:0.1-0.3:0.15-0.25:0.2-0.6.
[0019] Preferably, in step S1, the catalyst is boron trifluoride etherate.
[0020] Preferably, in step S1, the mass ratio of the silane coupling agent to ethanol is 1:1-2.
[0021] According to the preparation method, in step S1, the silane coupling agent reacts with diethyl maleate to introduce a carboxyl group; in step S2, the intermediate product reacts with epichlorohydrin to introduce an epoxy group. Both the carboxyl group and the epoxy group have high reactivity and can react chemically with the hydroxyl group on the surface of the nanomaterial to form a chemical bond. This greatly enhances the binding force between the nanomaterial and the modified silane coupling agent, so that the nanomaterial is better fixed in the coating, not easy to fall off or migrate, thereby improving the overall stability and durability of the nanocomposite layer. The presence of the epoxy group can form a flexible connecting bridge between the nanomaterial and the film-forming substance. When the coating is subjected to external force, the epoxy group can deform and rotate to a certain extent, absorb and dissipate energy, so that the nanocomposite layer has better elasticity and flexibility, reduces cracks and breakage caused by external force, and improves its impact resistance and bending resistance. The carboxyl group has a certain polarity and can be combined with the glass surface through hydrogen bonds or their interactions, thereby improving the adhesion of the nanocomposite layer to the glass substrate to a certain extent. This good adhesion helps to form a stable coating structure, making it difficult for the coating to fall off the glass surface, providing a basis for improving corrosion resistance. In a corrosive environment, the corrosion of glass is mainly caused by the hydrolysis of silicon-oxygen bonds on its surface by substances such as water, acid, and alkali. The carboxyl group can interact with some ions in the corrosive medium, such as forming a certain complex or electrostatic effect with hydrogen ions or hydroxide ions, thereby changing the chemical activity and diffusion properties of the corrosive medium. This can slow down the erosion rate of the corrosive medium on the glass surface to a certain extent, reduce the corrosion rate of the glass, and thus improve the corrosion resistance of the nanocomposite layer.
[0022] At the same time, the three-dimensional network structure formed after the epoxy group is cured has a high density, and this dense structure can also effectively block the diffusion and penetration of corrosive media such as water molecules, acids, alkalis and other substances to the glass surface. Since the corrosion of glass often starts from the surface and gradually develops inward, the dense network formed by the epoxy group is like a barrier, which greatly reduces the chance of contact between the corrosive medium and the glass surface, thereby significantly reducing the possibility of glass corrosion. The three-dimensional network structure formed by the epoxy group can also enhance the stability of the nanocomposite layer itself. During long-term use, the coating is not prone to degradation, decomposition or structural damage due to environmental factors. This stability enables the coating to continue to maintain its ability to block corrosive media, extend the protection time of the coating on the glass substrate, and further improve the corrosion resistance and service life of the nanocomposite layer. Furthermore, the introduced epoxy and carboxyl groups have good stability at high temperatures. In a high temperature environment, these groups can form stable chemical bonds and cross-linked structures to prevent the decomposition and degradation of the coating, maintain the integrity and performance stability of the coating, and enable the nanocomposite layer to still play a good protective role under high temperature conditions.
[0023] Preferably, in step (1) and step (2), the weight proportions of the nanomaterial, functional film-forming substance, dispersant, modified silane coupling agent and deionized water are: 60-90 parts of nanomaterial, 4-18 parts of functional film-forming substance, 8-15 parts of dispersant, 5-10 parts of modified silane coupling agent and 100-400 parts of deionized water.
[0024] Preferably, the nanomaterial is nano ZnO, nano TiO 2 、Nano-SiO 2 、Nano-SnO 2 、Nano Al 2 O 3 The weight ratio of each component is 1-3:0.5-1:1-1.5:1-1.2:0.16-0.36.
[0025] Preferably, the functional film-forming substance is one or more of phenolic resin, silicone-modified polyurethane, epoxy resin or alkyd resin.
[0026] Preferably, the functional film-forming substances are phenolic resin, silicone-modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin, among which the mass ratio of phenolic resin, silicone-modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin is 2-4:1-3:2-3:1-2.
[0027] Preferably, the dispersant is alkylphenol polyoxyethylene ether and polyether modified silicone oil, and the mass ratio of the two is 1:0.5-0.8.
[0028] Preferably, the ultrasonic treatment in step (1) has a frequency of 40-60 kHz and a duration of 60-120 min.
[0029] The present invention has the following beneficial effects:
[0030] The anti-cracking nanocomposite coating for a single non-insulating fireproof glass of the present invention forms a strong chemical bond by chemically reacting the carboxyl and epoxy groups in the modified silane coupling agent with the active groups on the surface of the nanomaterial, effectively combining the nanomaterials together to prevent them from agglomerating, and making the nanomaterials uniformly dispersed in the nanocomposite layer. Such uniformly dispersed nanomaterials can better exert their own performance advantages, such as nano ZnO, nano TiO 2 The photocatalytic and antibacterial properties of nano-SiO 2 、Nano Al 2 O 3 The modified silane coupling agent can improve the performance of the nanocomposite layer by improving the enhancement and wear resistance of the nanocomposite layer. The active groups such as epoxy groups of the modified silane coupling agent can undergo cross-linking reactions with the active groups in the functional film-forming material to form a three-dimensional network cross-linking structure. This cross-linking structure makes the nanocomposite layer more compact and improves the hardness, wear resistance and chemical corrosion resistance of the coating. The modified silane coupling agent plays a bridge role between the nanomaterial and the functional film-forming material. It closely combines the two together to form an organic whole between the nanomaterial and the functional film-forming material. This synergistic effect not only improves the various properties of the nanocomposite layer, but also improves its processing performance and construction performance, making it easier to prepare a uniform and stable coating, and can maintain good stability during use.
[0031] In summary, the method for preparing a crack-resistant nano-composite coating for a monolithic non-insulating fireproof glass provided by the present invention combines nano-materials with functional film-forming substances through a dispersant and a modified silane coupling agent. The nano-materials have high strength and hardness and can effectively enhance the mechanical properties of the coating. When the coating is subjected to external force, the nano-materials can bear part of the stress, reduce the crack propagation inside the coating, and thus improve the crack resistance of the coating. The nano-materials also have good heat insulation and high temperature resistance, prevent heat transfer and oxygen diffusion, thereby improving the fireproof performance of the coating and delaying the rupture time of the glass in a fire. The nano-materials can fill the pores and defects in the coating, make the coating more dense, prevent the intrusion of corrosive media, improve the corrosion resistance of the coating, and extend the service life of the fireproof glass. The functional film-forming substance cooperates with other components such as nano-materials and modified silane coupling agents to exert a synergistic effect. The film-forming substance works together with the nanomaterial to improve the fire resistance and mechanical properties of the coating; it cooperates with the modified silane coupling agent to enhance the interfacial bonding and stability of the coating, so that the coating has better crack resistance and service life, effectively improving the comprehensive performance and application value of the nanocomposite layer. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0033] The raw materials used in the following examples are all common commercial products. Among them, phenolic resin was purchased from Shandong Yonghui New Materials Co., Ltd., silicone-modified polyurethane was purchased from Oliron (Jining) Chemical Co., Ltd., bisphenol A epoxy resin, model NPEL-128, was purchased from Kunshan Jinkafu Chemical Co., Ltd., glycidyl ester epoxy resin, model EP-3950S, was purchased from Shanghai Kaiyin Chemical Co., Ltd., alkylphenol polyoxyethylene ether, model np-10, was purchased from Henan Qida Chemical Raw Materials Co., Ltd., and polyether-modified silicone oil, model DY-ET101, was purchased from Shandong Dayi Chemical Co., Ltd.
[0034] Example 1
[0035] A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass comprises the following steps:
[0036] Step (1), adding 12 parts of dispersant to 250 parts of deionized water, mixing, then adding 75 parts of nanomaterials thereto, and ultrasonically treating at a frequency of 50 kHz for 85 minutes to obtain a pretreated mixed material;
[0037] Step (2), adding 7 parts of modified silane coupling agent and 14 parts of functional film-forming material to the pretreated mixed material, stirring at a speed of 6000 rpm for 7 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by physical vapor deposition to form an anti-cracking nano-composite coating;
[0038] Wherein, the nano material is nano ZnO, nano TiO 2 、Nano-SiO 2 、Nano-SnO 2 、Nano Al 2 O 3 The weight ratio of each component is 2:0.8:1.2:1.1:0.30; the functional film-forming substances are phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin, among which the mass ratio of phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin is 3.5:2:2.5:1.5; the dispersant is alkylphenol polyoxyethylene ether and polyether modified silicone oil, and the mass ratio of the two is 1:0.7.
[0039] The preparation method of the modified silane coupling agent is as follows:
[0040] S1. Mix the silane coupling agent with ethanol, lower the temperature of the mixed solution to -10°C, add the catalyst boron trifluoride etherate, then drop diethyl maleate under stirring, react for 25 minutes after the addition, then raise the temperature to 22°C, react at a constant temperature for 1.5 hours, purify, and obtain an intermediate product;
[0041] S2. Add epichlorohydrin to the intermediate product of S1, react at 55°C for 3 hours, and distill under reduced pressure to remove excess epichlorohydrin to obtain a modified silane coupling agent.
[0042] In steps S1 and S2, the mass ratio of the silane coupling agent, ethanol, catalyst, diethyl maleate and epichlorohydrin is 1:1.5:0.2:0.2:0.4.
[0043] Example 2
[0044] A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass comprises the following steps:
[0045] Step (1), adding 8 parts of dispersant to 100 parts of deionized water, mixing, then adding 60 parts of nanomaterials thereto, and ultrasonically treating at a frequency of 60 kHz for 60 minutes to obtain a pretreated mixed material;
[0046] Step (2), adding 5 parts of a modified silane coupling agent and 10 parts of a functional film-forming substance to the pretreated mixed material, stirring at a speed of 5000 rpm for 8 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by chemical vapor deposition to form an anti-cracking nano-composite coating;
[0047] Wherein, the nano material is nano ZnO, nano TiO 2 、Nano-SiO 2 、Nano-SnO 2 、Nano Al 2 O 3 The weight ratio of each component is 1:0.6:1:1:0.25; the functional film-forming substances are phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin, among which the mass ratio of phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin is 3:3:3:2; the dispersant is alkylphenol polyoxyethylene ether and polyether modified silicone oil, and the mass ratio of the two is 1:0.5.
[0048] The preparation method of the modified silane coupling agent is as follows:
[0049] S1. Mix the silane coupling agent with ethanol, lower the temperature of the mixed solution to -15°C, add the catalyst boron trifluoride etherate, then drop diethyl maleate under stirring, react for 20 minutes after the addition, then raise the temperature to 20°C, react at a constant temperature for 2 hours, purify, and obtain an intermediate product;
[0050] S2. Add epichlorohydrin to the intermediate product of S1, react at 50°C for 4 hours, and distill under reduced pressure to remove excess epichlorohydrin to obtain a modified silane coupling agent.
[0051] In steps S1 and S2, the mass ratio of the silane coupling agent, ethanol, catalyst, diethyl maleate and epichlorohydrin is 1:1:0.1:0.15:0.26.
[0052] Example 3
[0053] A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass comprises the following steps:
[0054] Step (1), adding 15 parts of dispersant to 400 parts of deionized water, mixing, then adding 90 parts of nanomaterials thereto, and ultrasonically treating at a frequency of 40 kHz for 120 minutes to obtain a pretreated mixed material;
[0055] Step (2), adding 8 parts of modified silane coupling agent and 4 parts of functional film-forming material to the pretreated mixed material, stirring at a speed of 7000 rpm for 5 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by physical vapor deposition to form an anti-cracking nano-composite coating;
[0056] Wherein, the nano material is nano ZnO, nano TiO 2 、Nano-SiO 2 、Nano-SnO 2 、Nano Al 2 O 3 The weight ratio of each component is 3:1:1.5:1.2:0.16; the functional film-forming substances are phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin, among which the mass ratio of phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin is 2:1:2:1; the dispersant is alkylphenol polyoxyethylene ether and polyether modified silicone oil, and the mass ratio of the two is 1:0.8.
[0057] The preparation method of the modified silane coupling agent is as follows:
[0058] S1. Mix the silane coupling agent with ethanol, lower the temperature of the mixed solution to -5°C, add the catalyst boron trifluoride etherate, then drop diethyl maleate under stirring, react for 30 minutes after the addition, then raise the temperature to 25°C, react at a constant temperature for 1 hour, purify, and obtain an intermediate product;
[0059] S2. Add epichlorohydrin to the intermediate product of S1, react at 60°C for 24 hours, and distill under reduced pressure to remove excess epichlorohydrin to obtain a modified silane coupling agent.
[0060] In steps S1 and S2, the mass ratio of the silane coupling agent, ethanol, catalyst, diethyl maleate and epichlorohydrin is 1:1:0.3:0.25:0.6.
[0061] Example 4
[0062] A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass comprises the following steps:
[0063] Step (1), adding 11 parts of dispersant to 350 parts of deionized water, mixing, then adding 80 parts of nanomaterials thereto, and ultrasonically treating at a frequency of 55 kHz for 100 minutes to obtain a pretreated mixed material;
[0064] Step (2), adding 10 parts of a modified silane coupling agent and 18 parts of a functional film-forming substance to the pretreated mixed material, stirring at a speed of 6000 rpm for 6 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by chemical vapor deposition to form an anti-cracking nano-composite coating;
[0065] Wherein, the nano material is nano ZnO, nano TiO 2 、Nano-SiO 2 、Nano-SnO 2 、Nano Al 2 O 3 The weight ratio of each component is 2.6:0.5:1.4:1.1:0.36; the functional film-forming substances are phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin, among which the mass ratio of phenolic resin, silicone modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin is 4:1.5:2.2:1.8; the dispersant is alkylphenol polyoxyethylene ether and polyether modified silicone oil, and the mass ratio of the two is 1:0.6.
[0066] The preparation method of the modified silane coupling agent is as follows:
[0067] S1. Mix the silane coupling agent with ethanol, lower the temperature of the mixed solution to -9°C, add the catalyst boron trifluoride etherate, then drop diethyl maleate under stirring, react for 28 minutes after the addition, then raise the temperature to 23°C, react at a constant temperature for 1.8 hours, purify, and obtain an intermediate product;
[0068] S2. Add epichlorohydrin to the intermediate product of S1, react at 52° C. for 3.5 hours, and distill under reduced pressure to remove excess epichlorohydrin to obtain a modified silane coupling agent.
[0069] In steps S1 and S2, the mass ratio of the silane coupling agent, ethanol, catalyst, diethyl maleate and epichlorohydrin is 1:1.8:0.25:0.18:0.5.
[0070] Comparative Example 1
[0071] A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass comprises the following steps:
[0072] Step (1), adding 12 parts of dispersant to 250 parts of deionized water, mixing, then adding 75 parts of nanomaterials thereto, and ultrasonically treating at a frequency of 50 kHz for 85 minutes to obtain a pretreated mixed material;
[0073] Step (2), adding 7 parts of unmodified silane coupling agent and 14 parts of functional film-forming material to the pretreated mixed material, stirring at a speed of 6000 rpm for 7 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by physical vapor deposition to form an anti-cracking nano-composite coating;
[0074] The rest is the same as in Example 1.
[0075] Comparative Example 2
[0076] A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass comprises the following steps:
[0077] Step (1), adding 8 parts of dispersant to 100 parts of deionized water, mixing, then adding 60 parts of nanomaterials thereto, and ultrasonically treating at a frequency of 60 kHz for 60 minutes to obtain a pretreated mixed material;
[0078] Step (2), adding 5 parts of unmodified silane coupling agent and 10 parts of functional film-forming material to the pretreated mixed material, stirring at a speed of 5000 rpm for 8 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by chemical vapor deposition to form an anti-cracking nano-composite coating;
[0079] The rest is the same as Example 2.
[0080] Performance Testing:
[0081] According to GB15763.1-2009 "Safety Glass for Buildings Part 1: Fireproof Glass", the performance of the single non-insulating fireproof glass with anti-crack nano-composite coating obtained in Examples 1-4 and Comparative Examples 1-2 was tested. The test results are shown in Table 1.
[0082] Table 1. Performance parameters of single-piece non-insulating fire-resistant glass
[0083]
[0084] From the results in the above table, it can be seen that the nanocomposite coating obtained by the preparation method of the anti-crack nanocomposite coating for monolithic non-insulating fireproof glass of the present invention has a smooth surface quality, no microbubbles, a fire resistance completion time ≥190min, a light transmittance ≥89.45%, a resistance to ultraviolet radiation ≤1.9, good impact resistance, and no cracks, which are better than Comparative Examples 1 and 2.
[0085] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0086] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a crack-resistant nanocomposite coating for a single piece of non-insulating fireproof glass, characterized in that: The following steps are involved: Step (1), adding a dispersant to deionized water, mixing, then adding the nanomaterial, and ultrasonically treating to obtain a pretreated mixed material; Step (2), adding a modified silane coupling agent and a functional film-forming substance to the pretreated mixed material, stirring at a speed of 5000-7000 rpm for 5-8 minutes to obtain a nano-composite coating, and then depositing the nano-composite coating on the surface of a single piece of non-insulating fireproof glass by physical vapor deposition or chemical vapor deposition to form an anti-cracking nano-composite coating; The preparation method of the modified silane coupling agent is as follows: S1. Mix the silane coupling agent with ethanol, lower the temperature of the mixed solution to -15 to -5°C, add a catalyst, and then drop diethyl maleate under stirring. After the addition, react for 20-30 minutes, then raise the temperature to 20-25°C, react at a constant temperature for 1-2 hours, and purify to obtain an intermediate product; S2. Add epichlorohydrin to the intermediate product of S1, react at a temperature of 50-60° C. for 2-4 hours, and distill under reduced pressure to remove excess epichlorohydrin to obtain a modified silane coupling agent.
2. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: In steps S1 and S2, the mass ratio of the silane coupling agent, the catalyst, diethyl maleate and epichlorohydrin is 1:0.1-0.3:0.15-0.25:0.2-0.
6.
3. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: In step S1, the catalyst is boron trifluoride etherate.
4. The method for preparing the anti-crack nanocomposite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: In step S1, the mass ratio of the silane coupling agent to ethanol is 1:1-2.
5. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: In step (1) and step (2), the weight proportions of the nanomaterial, functional film-forming substance, dispersant, modified silane coupling agent and deionized water are as follows: 60-90 parts of nanomaterial, 4-18 parts of functional film-forming substance, 8-15 parts of dispersant, 5-10 parts of modified silane coupling agent and 100-400 parts of deionized water.
6. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: The nano materials are nano ZnO, nano TiO2, nano SiO2, nano SnO2, and nano Al2O3, and the weight ratio of each component is 1-3: 0.5-1:1-1.5:1-1.2:0.16-0.36。 7. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: The functional film-forming substance is one or more of phenolic resin, silicone-modified polyurethane, epoxy resin or alkyd resin.
8. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 7, characterized in that: The functional film-forming substances are phenolic resin, silicone-modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin. The mass ratio of phenolic resin, silicone-modified polyurethane, bisphenol A epoxy resin, and glycidyl ester epoxy resin is 2-4:1-3:2-3:1-2.
9. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: The dispersant is alkylphenol polyoxyethylene ether and polyether modified silicone oil, and the mass ratio of the two is 1:0.5-0.
8.
10. The method for preparing the anti-crack nano-composite coating for a single piece of non-insulating fireproof glass according to claim 1, characterized in that: In step (1), the ultrasonic treatment is performed at a frequency of 40-60 kHz and for a time of 60-120 min.
Citation Information
Patent Citations
Fireproof layer material and preparation method thereof and non-insulating composite fireproof glass
CN115521081B
Fireproof coating, preparation method thereof and fireproof glass
CN116445021A
High-wear-resistant and weather-resistant coating for automobile and preparation method thereof
CN113150634A
Crystalline modified polylactic acid material and preparation method thereof
CN116554661A
Fireproof water-based paint for interior and exterior walls and preparation method of fireproof water-based paint
CN118995004A
Cited By
Single-sheet heat-insulation fireproof glass composite coating and preparation method thereof
CN120081600A